2013
DOI: 10.1155/2013/746281
|View full text |Cite
|
Sign up to set email alerts
|

Irisin, Two Years Later

Abstract: In January 2012, Boström and colleagues identified a new muscle tissue secreted peptide, which they named irisin, to highlight its role as a messenger that comes from skeletal muscle to other parts of the body. Irisin is a cleaved and secreted fragment of FNDC5 (also known as FRCP2 and PeP), a member of fibronectin type III repeat containing gene family. Major interest in this protein arose because of its great therapeutic potential in diabetes and perhaps also therapy for obesity. Here we review the most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 62 publications
2
101
0
3
Order By: Relevance
“…These data support the assumption that the energy taken in is burnt, and the irisin significantly prevents the development of obesity [18]. The fact that the irisin encourages brown fat development, and its decreasing the body weight by increasing heat production shows that the peptide has anti obesity properties [19]. The irisin encouraging the brown fat development and decreasing the obesity, and its existence in testes and epididymis tissue and its roles in different cancer types [20] make us think that the peptide is effective in prostate cancer as well.…”
Section: Introductionsupporting
confidence: 81%
“…These data support the assumption that the energy taken in is burnt, and the irisin significantly prevents the development of obesity [18]. The fact that the irisin encourages brown fat development, and its decreasing the body weight by increasing heat production shows that the peptide has anti obesity properties [19]. The irisin encouraging the brown fat development and decreasing the obesity, and its existence in testes and epididymis tissue and its roles in different cancer types [20] make us think that the peptide is effective in prostate cancer as well.…”
Section: Introductionsupporting
confidence: 81%
“…Alternatively, it may be linked to a higher order of trainingassociated regulation, perhaps mediated through systemic factors. Irrespective of the underlying mechanism, the relationship suggests that s-irisin is conditionally controlled by training in humans, as was also suggested by Novelle et al (2013), emphasizing that there is more to irisin biology than can be concluded from population-based studies. Importantly, the relationship between trainingassociated changes in s-irisin and LBM was insensitive to the type of strength training protocol, as it was equally prominent in combined 3L1U/1L3U data as it was in separate 3L1U and 1L3U data, despite very low statistical powers of these latter analyses (n=6 in each group, data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…), as was reported by Wen et al (32). Moreover, irisin synthesis might also decrease due to decreased muscle mass in CKD (34), as it is known that the irisin level is positively correlated with muscle mass (35); however, this hypothesis could not be proven in the present study because muscle mass was not measured. Another hypothesis is that low physical activity in CKD patients, especially those on hemodialysis (36), might cause exercise-dependent irisin hormone to be lower than in sedentary healthy individuals.…”
Section: Discussionmentioning
confidence: 42%